Progressive Muscle Relaxation Therapy in Patients at Risk of Violent Behavior: A Case Study - Sovianti, Vivi; Jona, Resa Nirmala; Juwariyah, Siti; Septianingtyas, Maya Cobalt Angio (Universitas Muhammadiyah Semarang, 2024)
Risk of Violent Behavior is one of the responses toward stressor dealt by an individual who experiences the decline of ability in solving problem, being oriented in time, place or person and feeling anxious. The purpose of this study case is to acknowledge the symptoms and signs of patients with risk of violent behavior before and after they receive exercise of progressive muscle relaxation. Symptoms of violent behavior experienced on patient I were: he was angry, yelled and slam something, because he cannot stand of being farmer and poor. Symptoms of violent behavior experienced on patient II were: Patien was angry and violent. He threw objects at home, hit his parents, had sleep difficulty, felt anxious, walked randoomly and intended to burn house since 5 days ago. The patient's diagnosis was schizophrenia with violent behavior. Intervension in this study used progressive muscle relaxation (PMR). Intervention was done for four days. It was given once a meeting and progressive muscle relaxation was done for 30 minutes. The difference of symptoms and signs before and after progressive muscle relaxation therapy was given can be seen based on the result of pre and post in both subjects. A decrease in symptoms and signs after progressive muscle relaxation therapy is a success of this therapy in controlling violent behavior, but this therapy must be carried out on cooperative patients.